2019
DOI: 10.3390/f10070597
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Microtopography and Soil Treatments on Tree Establishment on a Reclaimed Quarry

Abstract: Research Highlights: Reclaimed minesites provide an opportunity to establish plantings of tree species of special concern, such as the American chestnut (Castanea dentata (Marshall) Borkh.), white oak (Quercus alba L.) and shortleaf pine (Pinus echinata Mill.). Background and Objectives: Reforestation success may be influenced by the physical and chemical characteristics of the substrate, which can be manipulated as part of the reclamation process. The objective of this study was to test the effects of three c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Other authors (Barberá et al, 2005; Ortiz et al, 2012), also found organic amendments as the most effective growth enhancers for pine reforestation in Mediterranean degraded ecosystems as well as in much wetter environments like those of the Appalachian (Franklin & Bickley, 2019) or Canada (Hahn & Quideau, 2013; Larney & Angers, 2011). Fuentes et al (2010) indicated that low to moderate doses of sewage sludge, similar to those used in this research, showed the best combination of seedling survival and growth promoting P. halepensis establishment in dry Mediterranean areas.…”
Section: Discussionmentioning
confidence: 93%
“…Other authors (Barberá et al, 2005; Ortiz et al, 2012), also found organic amendments as the most effective growth enhancers for pine reforestation in Mediterranean degraded ecosystems as well as in much wetter environments like those of the Appalachian (Franklin & Bickley, 2019) or Canada (Hahn & Quideau, 2013; Larney & Angers, 2011). Fuentes et al (2010) indicated that low to moderate doses of sewage sludge, similar to those used in this research, showed the best combination of seedling survival and growth promoting P. halepensis establishment in dry Mediterranean areas.…”
Section: Discussionmentioning
confidence: 93%